Towards a new set of classification criteria for PFAPA syndrome - Federica Vanoni; Roberta Caorsi; Sandra Aeby; Marie Cochard; Jordi Antón; Stefan Berg; Riva Brik; Pavla Dolezalova; Isabelle Koné-Paut; Benedicte Neven; Seza Ozen; Pascal Pillet; et al. (BMC, 2018)
Abstract Background Diagnosis of Periodic Fever, Aphthous stomatitis, Pharyngitis and Cervical Adenitis (PFAPA) syndrome is currently based on the modified Marshall's criteria, but no validated evidence based classification criteria for PFAPA has been established so far. Methods A multistep process, based on the Delphi and Nominal Group Technique was conducted. After 2 rounds of e-mail Delphi survey involving 21 experts in autoinflammation we obtained a list of variables that were discussed in an International Consensus Conference. Variables reaching the 80% of consensus between participants were included in the new classification criteria. In the second phase the new classification criteria and the modified Marshall's criteria were applied on a cohort of 80 pediatric PFAPA patients to compare their performance. Results The Delphi Survey was sent to 22 participants, 21 accepted to participate. Thirty variables were obtained from the survey and have been discussed at the Consensus Conference. Through the Nominal Group Technique we obtained a new set of classification criteria. These criteria were more restrictive in respect to the modified Marshall's criteria when applied on our cohort of patients. Conclusion Our work led us to identify a new set of classification criteria for PFAPA syndrome, but they resulted to be too restrictive to be applied in daily clinical practice for the diagnosis of PFAPA.